Changes in Serum Concentrations of Fibroblast Growth Factor 23 and Soluble Klotho in Hemodialysis Patients after Total Parathyroidectomy. (24th November 2016) - Liao, Shang-Chih; Moi, Sin-Hua; Chou, Fong-Fu; Yang, Cheng-Hong; Chen, Jin-Bor
Abstract : Background . We examined the changes in circulating fibroblast growth factor 23 (FGF23) and Klotho concentrations in hemodialysis patients after parathyroidectomy (PTX). Methods . We enrolled a cohort of hemodialysis patients who received PTX. Postoperatively, patients received calcium supplements and/or vitamin D analogue (calcitriol) to maintain serum calcium within 7.0–8.0 mg/dL. Information on clinical parameters including bone-mineral metabolic variables was collected pre-PTX and on days 5 and 90 after PTX. Concomitantly, serum full-length FGF23 and α -Klotho levels were measured. The relationship between FGF23 and clinical parameters was analyzed by single linear regression. Results . Forty-six participants (33 women; 13 men) were enrolled in the study. Their mean age was 56.49 years. Serum FGF23 and α -Klotho concentrations were elevated on days 5 and 90 after PTX compared to baseline (p > 0.05 ). Serum FGF23 concentrations negatively correlated with serum calcium concentrations pre-PTX (Beta - 0.31 ; R 2 0.0949; p = 0.040 ), day 5 post-PTX (Beta - 0.31 ; R 2 0.0982; p = 0.036 ), and day 90 post-PTX (Beta - 0.39 ; R 2 0.1528; p = 0.008 ). Conclusions . There was no change in circulating FGF23 and Klotho concentrations after PTX in hemodialysis patients given postoperative calcium supplements and/or vitamin D analogue. Serum FGF23 concentrations pre-PTX and at days 5 and 90 after PTX were inversely related to serum calcium concentrations.